Plasma lipidome profiling of newborns with antenatal exposure to Zika virus. - Nieli Rodrigues da Costa Faria; Adriano Britto Chaves-Filho; Luiz Carlos Junior Alcantara; Isadora Cristina de Siqueira; Juan Ignacio Calcagno; Sayuri Miyamoto; Ana Maria Bispo de Filippis; Marcos Yukio Yoshinaga (Public Library of Science (PLoS), 2021)
The 2015-2016 Zika virus (ZIKV) outbreak in Brazil was remarkably linked to the incidence of microcephaly and other deleterious clinical manifestations, including eye abnormalities, in newborns. It is known that ZIKV targets the placenta, triggering an inflammatory profile that may cause placental insufficiency. Transplacental lipid transport is delicately regulated during pregnancy and deficiency on the delivery of lipids such as arachidonic and docosahexaenoic acids may lead to deficits in both brain and retina during fetal development. Here, plasma lipidome profiles of ZIKV exposed microcephalic and normocephalic newborns were compared to non-infected controls. Our results reveal major alterations in circulating lipids from both ZIKV exposed newborns with and without microcephaly relative to controls. In newborns with microcephaly, the plasma concentrations of hydroxyoctadecadienoic acid (HODE), primarily as 13-HODE isomer, derived from linoleic acid were higher as compared to normocephalic ZIKV exposed newborns and controls. Total HODE concentrations were also positively associated with levels of other oxidized lipids and several circulating free fatty acids in newborns, indicating a possible plasma lipidome signature of microcephaly. Moreover, higher concentrations of lysophosphatidylcholine in ZIKV exposed normocephalic newborns relative to controls suggest a potential disruption of polyunsaturated fatty acids transport across the blood-brain barrier of fetuses. The latter data is particularly important given the neurocognitive and neurodevelopmental abnormalities observed in follow-up studies involving children with antenatal ZIKV exposure, but normocephalic at birth. Taken together, our data reveal that plasma lipidome alterations associated with antenatal exposure to ZIKV could contribute to identification and monitoring of the wide spectrum of clinical phenotypes at birth and further, during childhood.